Diagnosis and management of pancreatic cancer in adults: A summary of guidelines from the UK National Institute for Health and Care Excellence - O'Reilly, Derek; Fou, Linyun; Hasler, Elise; Hawkins, James; O'Connell, Susan; Pelone, Ferruccio; Callaway, Mark; Campbell, Fiona; Capel, Margred; Charnley, Richard; Corrie, Pippa; Elliot, Dawn; et al. (Pancreatology, 2018)
To enable standardisation of care of pancreatic cancer patients and facilitate improvement in outcome, the United Kingdom's National Institute for Health and Care Excellence (NICE) developed a clinical guideline for the diagnosis and management of pancreatic cancer in adults. Systematic literature searches, systematic review and meta-analyses were undertaken. Recommendations were drafted on the basis of the group's interpretation of the best available evidence of clinical and cost effectiveness. There was patient involvement and public consultation. Recommendations were made on: diagnosis; staging; monitoring of inherited high risk; psychological support; pain; nutrition management; and the specific management of people with resectable-, borderline-resectable- and unresectable-pancreatic cancer. The guideline committee also made recommendations for future research into neoadjuvant therapy, cachexia interventions, minimally invasive pancreatectomy, pain management and psychological support needs. These NICE guidelines aim to promote best current practice and support and stimulate research and innovation in pancreatic cancer.